2018
DOI: 10.2147/ijn.s159388
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of oxidative stress, apoptosis, and autophagy involved in graphene oxide nanomaterial anti-osteosarcoma effect

Abstract: BackgroundGraphene and its derivative graphene oxide (GO) have been implicated in a wide range of anticancer effects.PurposeThe objective of this study was to systematically evaluate the toxicity and underlying mechanisms of GO on two osteosarcoma (OSA) cancer cell lines, MG-63 and K7M2 cells.MethodsMG-63 and K7M2 cells were treated by GO (0–50 µg/mL) for various time periods. Cell viability was tested by MTT and Live/Dead assays. A ROS Detection Kit based on DHE oxidative reaction was used for ROS detection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 34 publications
4
53
1
Order By: Relevance
“…Moreover, flow cytometry analysis showed that GO induced cell cycle arrest. A previous study reported that graphene derivatives could promote apoptosis in osteosarcoma [31]. Our data showed that GO induced apoptosis Fig.…”
Section: Discussionsupporting
confidence: 65%
“…Moreover, flow cytometry analysis showed that GO induced cell cycle arrest. A previous study reported that graphene derivatives could promote apoptosis in osteosarcoma [31]. Our data showed that GO induced apoptosis Fig.…”
Section: Discussionsupporting
confidence: 65%
“…They found that the cytotoxicity was dependent on GO sheet size for NIH 3T3, U87, and A549 cells, while little effect of sheet size on toxicity for RAW 264.7, NB4, and HL60 cell lines. Previous research reported that the production of ROS is one of the important mechanisms for the toxicity of nanoparticles (Khatri et al, 2013;Seabra et al, 2014;Tang et al, 2018). Nanoparticles interfere with oxidative balance of cell and cause oxidative stress to generate reactive oxygen species, such as superoxide, hydroxyl radical, peroxide radical, hydrogen peroxide, and singlet oxygen (Yan et al, 2017;Lu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…mitoTEMPO (200 μM, Sigma-Aldrich, SML0737) was added for 2 h before glucose treatment to scavenge the mtROS (Chen et al 2018). In addition, pretreatment with the antagonist ML385 (10 μM, Abcam, ab120843) (Tang et al 2018) was done for 2 h every day before CoQ10 administration to inhibit Nrf2.…”
Section: Cell Culturementioning
confidence: 99%